Biological Interfaces, Modulation, and Sensing with Inorganic Nano‐Bioelectronic Materials. Issue 5 (8th March 2020) - Schaumann, Erik N.; Tian, Bozhi
Abstract: The last several years have seen a large and increasing interest in scientific developments that combine methods and materials from nanotechnology with questions and applications in bioelectronics. This follows with a number of broader trends: the rapid increase in functionality for materials at the nanoscale; a growing recognition of the importance of electric fields in diverse physiological processes; and continuous improvements in technologies that are naturally complementary with bioelectronics, such as optogenetics. Here, a progress report is provided on several of the most exciting recent developments in this field. The three critical functions of biointerface formation, biological modulation, and biological sensing using newly developed nanoscale materials are considered. Abstract : Inorganic nanomaterials constitute a promising class of materials for engineering biological interactions. Within the space of bioelectronic applications, they offer the promise of a wide variety of forms and functions, including both intracellular and extracellular modulation and sensing. This progress report discusses several of the exciting recent developments in this field.